2012
DOI: 10.1007/s10144-012-0307-8
|View full text |Cite
|
Sign up to set email alerts
|

Ruderality in extreme‐desert cacti? Population effects of chronic anthropogenic disturbance on Echinocereus lindsayi

Abstract: Ruderal species, i.e., those that increase their numbers in the presence of disturbance, are not expected to occur in extreme environments. We test whether Echinocereus lindsayi, a cactus from an extreme desert, follows the ruderal trend observed in similar species from mild deserts, or, as theory suggests, it is a non ruderal. Contrary to expectations, its density and fraction of small individuals in the population increased with disturbance. This seemingly results from increased establishment, as it is nurse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 66 publications
1
7
0
1
Order By: Relevance
“…Studies at the population level have shown positive, negative or neutral effects of disturbance in cacti density. Some species (called ruderal cacti sensu Martorell and Peters, 2005) may benefi t from moderate levels of human activities as the globose species Coryphantha werdermannii in Coahuila, North Mexico (Portilla-Alonso and Martorell, 2011) and the cylindrical cactus Echinocereus lindsayi in Baja California, Mexico (Martorell et al, 2012). In the present study, further analysis at species level revealed that Opuntia velutina and O. puberula were significantly more abundant in the secondary forest under chronic disturbance compared to the conserved forest (t (1,10) = 2.6, P < 0.05 and t (1,10) = 6.4, P < 0.0001, respectively).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies at the population level have shown positive, negative or neutral effects of disturbance in cacti density. Some species (called ruderal cacti sensu Martorell and Peters, 2005) may benefi t from moderate levels of human activities as the globose species Coryphantha werdermannii in Coahuila, North Mexico (Portilla-Alonso and Martorell, 2011) and the cylindrical cactus Echinocereus lindsayi in Baja California, Mexico (Martorell et al, 2012). In the present study, further analysis at species level revealed that Opuntia velutina and O. puberula were significantly more abundant in the secondary forest under chronic disturbance compared to the conserved forest (t (1,10) = 2.6, P < 0.05 and t (1,10) = 6.4, P < 0.0001, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…These results are in line with others studies at population level; for example for Ferocactus histrix (del Castillo, 1987) and Coryphantha werdermannii (Portilla-Alonso and Martorell, 2011), a higher proportion of adults were found at the sites with less chronic disturbance. The proportion of adults under conditions of chronic disturbance may decrease due to high mortality of small size-classes and slow growth rates (Jiménez-Sierra et al, 2007;Alba-García, 2011;Martorell et al, 2012). Also, some studies have shown that even when recruitment is higher in grasslands, cacti growth faster in sites denuded of grasses (Mandujano et al, 2001) because belowground competition (Briones et al, 1996).…”
Section: Luís Antonio Arias-medellín Et Almentioning
confidence: 99%
“…We estimated the λ s value of each harvest scenario by iterating the kernels 1000 times, out of which we took the last 900 λ values so that the simulation model reached its stationary ergodic properties (Martorell et al . ), to obtain the geometric mean of lambda. To obtain the number remaining adults, we obtained the first 100 iterations of the IPM population structure proportions, starting with the observed size structures.…”
Section: Methodsmentioning
confidence: 99%
“…In this paper, we used Integral Projection Models (IPMs, Ellner & Rees ), a relatively novel approach in plant demography to project harvest impact, because it provides smaller confidence intervals in the parameters estimation since the model uses continuous variables and the variation in all the individuals and avoids size‐class subjective categorization (Martorell et al . ).…”
mentioning
confidence: 97%
“…To mention but one, altitude ranged from 640 to 2500 m a.s.l. Third, climate fluctuations are important in drylands (Schwinning et al 2004), and thus vital rates are not likely to be deterministic (Fieberg and Ellner 2001;Martorell et al 2012) as assumed by our model. Furthermore, given that we are working with an endangered species, the samples were relatively small (130 AE 97 individuals per site), limiting the amount of information supplied to the model.…”
Section: Real Species: a Challengementioning
confidence: 98%